Food crisis risk monitoring: Early warning for early action - Greb, Friederike (2023)
Friederike Greb GLOBAL FOOD POLICY REPORT 2023 Global Food Policy Report: Rethinking Food Crisis Responses Hybrid Global Launch Event APR 13, 2023 - 9:00 TO 10:30AM EDT